The Effect of Sox9 on Cell Growth and Stemness in HER2-Positive Breast Cancer - Zuccarini, Riana (Université d'Ottawa / University of Ottawa, 2025)
Breast cancer is one of the most diagnosed and fatal malignancies, and its incidence increases each year. The HER2-positive subtype is associated with aggressive disease and poor outcome, with a high risk of acquired resistance to first-line treatment. A key contributor to these qualities is epithelial-to-mesenchymal transition (EMT). Sox9 has been linked to tumorigenesis and EMT in many cancers, but its role in HER2-positive breast cancer has yet to be fully characterized. Previous studies have identified a gene network downstream of HER2 that promotes a stem-like phenotype in vitro and reduces overall survival in vivo due to Sox10 upregulation through a PDK1-AKT-Sox9 axis, and we have shown that Sox10 deletion reduces stemness and inhibits hyperplasia. We hypothesized that Sox9 drives a distinct genetic program required for invasion and the maintenance of stem cells. To determine the effect of Sox9 on cell phenotype we have generated Sox9-deficient cells with a CRISPR/Cas9 knockout and Sox9-overexpressing cells by lentiviral transduction. In vitro characterization of these cells demonstrated significant decreases in proliferation, sphere-forming, and invasion in the Sox9-deficient cells with stronger effects observed in complete knockout cells compared to those with residual Sox9 expression. RNA-sequencing revealed an upregulation of epithelial-associated genes in Sox9-deficient cells. Lastly, we have shown that Sox9-deficiency inhibits expansion in vivo using orthotopic and tail-vein injection models. Together, our findings suggest that Sox9-knockout inhibits stemness in HER2-positive tumour-derived cells. Further insight into the role of Sox9 may reveal novel therapeutic targets for breast cancer treatment.
Keywords: Breast cancer; Sox9; HER2; Cancer stem cell